Immune responses against norovirus GII.4 virus-like particles in mice - Ushijima H. (2017)
Norovirus (NoV) is a causative agent of gastroenteritis in children and adults worldwide. To evaluate the safety and effectiveness of a NoV vaccine candidate, 100 μg of GII.4 NoV-like particles (VLPs) was challenged orally (oral and intrabuccal administration) and by subcutaneous injection without adjuvant in mice. The subcutaneous injection induced IgG in sera, but not IgA in feces. The oral delivery method induced IgA in both sera and feces, but not IgG in sera. However, challenging by the intrabuccal administration induced IgG in sera and IgA in both sera and feces, especially by 2-dose immunization. The peak of specific immune responses by the intrabuccal administration was detected later than that of the oral delivery method. Heterologous immune responses against other genotypes were also recognized. NoV-specific IFN-γ was detected after the intrabuccal administration. These findings indicated that the administration of NoV VLPs by intrabuccal administration could induce the best immune responses against NoV in mice.